Long-Term Outcomes and Risk Factors for Lymph Node Metastasis in Siewert Type II/III Early Gastric Cancer - Min Young Son; Dae Hyeon Cho; Sung Eun Kim; Seun Ja Park; Moo In Park; Won Moon; Jae Hyun Kim; Jung Wook Lee; Kyoungwon Jung (Yong Chan Lee, 2024)
Objectives The incidence of adenocarcinomas of the esophagogastric junction (EGJ) and cardia has been gradually increasing in the East. Cancers of the EGJ and gastric cardia have poor prognoses. This study aimed to investigate lymph node metastasis (LNM) rates, their predictive factors, and determine the long-term outcomes of patients with Siewert type II/III early gastric cancer (EGC). Methods Between January 2014 and June 2022, a total of 573 patients with gastric cancer, including 130 with Siewert type II/III EGC, underwent total gastrectomies at the Kosin University Gospel Hospital. Factors associated with LNM were analyzed using a logistic regression model. Results Of the 130 patients with Siewert type II/III EGC, 10 (7.7%) demonstrated LNM (LNM-positive group). Macroscopically elevated lesions (I+IIa) (60.0% vs. 16.7%; p=0.009) and lymphovascular invasion (70.0% vs. 5.8%; p<0.001) were more common and the depth of invasion was deeper (p=0.003) in the LNM-positive patients than in the LNMnegative group. Multivariate analysis showed that macroscopically elevated lesions (odds ratio [OR], 19.48; 95% confidence interval [CI], 1.93-197.11; p=0.012) and lymphovascular invasion (OR, 52.63; 95% CI, 5.26-526.51; p=0.001) were associated with LNM. Kaplan-Meier analysis revealed that the 5-year overall and disease-specific survival rates of patients with Siewert type II/III EGC were 90.0% and 98.9%, respectively. During a median follow-up period of 49 months (range, 12-122 months), one patient (0.8%) died owing to gastric cancer recurrence. Conclusions Patients with Siewert type II/III EGC showed favorable long-term outcomes. Macroscopically elevated lesions and lymphovascular invasion are associated with LNM.